Evaluation of nine pesticide residues in three minor tropical fruits from southern China. (February 2016) - Yang, Xinfeng; Luo, Jinhui; Li, Shuhuai; Liu, Chuanhua
Abstract: The residue levels of nine pesticides (imidacloprid, acetamiprid, carbendazim, diflubenzuron, chlorbenzuron, phoxim, pyrimethanil, abamectin and iprodione) in 117 samples of three minor tropical fruits (starfruits, wax apples and Indian jujubes) from Hainan, Fujian, Guangdong and Guangxi provinces in China were analyzed using ultra-high performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) after multi-residue extraction procedures. A total of 78 (66.7%) samples were positive, with residues above the limit of quantification. Indian jujube was the fruit with the highest percentage of positive samples (81.6%), followed by starfruit (61.0%) and finally wax apple (57.9%). Carbendazim was the most frequently detected residue found in 51 (43.6%) samples in the concentration ranges of 34.0–443.8 μg/kg. Diflubenzuron, phoxim, pyrimethanil and abamectin were not detected in any sample. Twenty-nine (24.8%) samples were contaminated with multiple pesticide residues, and the simultaneous occurrence of three different residues was found in one wax apple and two starfruit samples. Estimation of the potential health risks associated with the exposure to the analyzed pesticides was carried out and the estimated daily intakes (EDIs) were very low, ranging from 0.020% of the acceptable daily intakes (ADIs) for chlorbenzuron to 1.13% for carbendazim. These results indicate that despite a high occurrence of pesticides in starfruit, wax apple and Indian jujube, the contamination levels do not contribute significantly to pesticide intakes and are unlikely to have public health effects. Nevertheless, measures should be taken to hasten the registration of pesticides for use on minor fruit crops. The findings also indicate that routine monitoring of pesticide residues in minor fruits is necessary to prevent, control and reduce pesticide contamination and to minimize health risks. Highlights: This work focused on pesticide residues in three minor tropical fruits. A high rate of occurrence (66.7%) of pesticides was found in the samples. Most minor fruit samples contained un-registered pesticides. The risk levels from fruit consumption were lower than permissible values.